Dominant spatial patterns of interannual variability in summer precipitation across northern Eurasia from Coupled Model Intercomparison Project Phase 5 models. (18th January 2022) - Abe, Manabu; Fujinami, Hatsuki; Hiyama, Tetsuya
Abstract: There is a lack of studies elucidating the characteristics of interannual variability in different models, especially for northern Eurasia. Therefore, spatial patterns of interannual variability in summer precipitation over northern Eurasia across 15 models of Coupled Model Intercomparison Project Phase 5 (CMIP5) were investigated using empirical orthogonal function (EOF) analysis and cluster analysis. The spatial patterns of EOF1‐3 obtained from the models exhibited similar features across the models. The spatial pattern characteristics of the interannual variability of models were similar to those of the actual observations. However, their contribution rates and the order of magnitude of the EOFs in each model differ among models and from observations. Despite the similarity between the patterns of the EOF in the models and the observations, the atmospheric circulations causing the pattern differed in the models and actual observations, resulting in uncertainty in the models. This indicates that in the analysis of extreme events and their impact, the reproducibility and uncertainty of climate models with regard to interannual variability need to be adequately evaluated. In addition, similar to many climate models, the spatial pattern of interannual variability, which is different from any of EOF1‐3 for the observations, has been more strongly represented than the actual observations. Clarification of the factors governing the common but unsuitable variability across models may be expected to decrease the uncertainty of the models in terms of interannual variability. Abstract : Due to a lack of studies elucidating the characteristics of internal variability in northern Eurasia for different models, spatial patterns of interannual variability in summer precipitation over northern Eurasia across 15 climate models were investigated. The similarity between the patterns of the EOF in the models and the observations, but the atmospheric circulations causing the pattern differed in the models and actual observations. Therefore, the uncertainty of climate models with regard to interannual variability need to be adequately evaluated.